UTILIZING AUDIO VISUAL AIDS TO IMPROVE ENGLISH SPEAKING SKILL FOR THE EIGHT GRADE STUDENTS OF SMP NEGERI 3 BANAWA - Irmawati Irmawati; Muhammad Ihsan; Rasmi Rasmi (Datokarama English Education Journal, 2020)
This study aims to improve the speaking skill of the eighth grade students of SMP Negeri 3 Banawa in the use of audio visual aids. This research was conducted through action research consisting of two cycles. The data were obtained from observation during the implementation of the action; interview with Teacher of English and the eighth grade students from class VIII A; and discussion with Teacher of English. Data in the form of field notes, interview transcripts, and photographs. The validity of the data is obtained by applying utilization Audio Visual Aids, results and processes. The results show that there was an increase in students' speaking skills through the use of audio visual aids. The audio-visual tool used in this study was video and slide. Videos were taken from youtube.com in the form of dialogue in certain expressions. These videos can attract students' attention and increase their learning motivation. Students can have a better understanding of the use of English in real situations when they learn appropriate Englishlanguage models through audio-visual aids (video and slide). Students make improvements in several aspects of speaking skills, such as fluency and comprehensibility. They are more confident in speaking English. They actively participate during the teaching and learning process. In addition, they did not hesitate to ask the teacher when they found difficulties. The research findings are also supported by the results of students' speaking achievement which increased from 57.78 in cycle I to 72.67 in cycle II.